2011
DOI: 10.1039/c1an15125h
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular features revealed on unfixed rat brain sections by phase imaging

Abstract: For sectioned biologic tissues, atomic force microscopy (AFM) topographic images alone hardly provide adequate information leading to revealing biological structures. We demonstrate that phase imaging in amplitude-modulation AFM is a powerful tool in mapping structures present on the surface of unfixed rat brains sections. The contrast in phase images is originated from the difference in mechanical properties between biological structures. Visualization of the native state of biological structures by way of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Indeed, understanding the physical topographical organization of the cortex has proven difficult owning to its gel-like consistency. Our findings correspond to the work by (Nie et al, 2011), even if their the measures published were only on 5 2 µm 2 or 10 2 µm 2 areas, and expand on these observations as we were able to record contact mode images on 100 2 µm 2 areas, in liquid environment, and on paraffin embedded slices that allowed for greater sensitivity in the acquisition of topography images. Atomic force microscopy contact mode measures permit for the assessment of surface topography and properties at nanometer scale.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, understanding the physical topographical organization of the cortex has proven difficult owning to its gel-like consistency. Our findings correspond to the work by (Nie et al, 2011), even if their the measures published were only on 5 2 µm 2 or 10 2 µm 2 areas, and expand on these observations as we were able to record contact mode images on 100 2 µm 2 areas, in liquid environment, and on paraffin embedded slices that allowed for greater sensitivity in the acquisition of topography images. Atomic force microscopy contact mode measures permit for the assessment of surface topography and properties at nanometer scale.…”
Section: Discussionsupporting
confidence: 89%
“…While much effort is now placed on understanding the biomechanical properties of CNS tissues, we sought to determine whether we could use topographical nanometric mapping to image and quantify the process of maturation occurring at the PSSC layers. One previous study (Nie et al, 2011) employed the amplitude modulation mode to explored unfixed, cryopreserved rat brain sections to obtain phase images allowing for the first time a topographical image of the cortex. These AFM experiments were conducted in air (40 % humidity) and only on 5 2 µm 2 or 10 2 µm 2 areas.The authors demonstrated that AFM phase images were sensitive to subcellular features, which the authors attributed to mechanical contrast, yet nanoscale structural mapping of larger areas was difficult owing to the glycolipid/glycoprotein nature of brain slices.…”
Section: Discussionmentioning
confidence: 99%
“…By phase contrast imaging of C. albicans after Ps d1 treatment, it was possible to distinguish some changes related to sample properties such as stiffness and softness (Magonov et al, 1997; Martinez and Garcia, 2006; Garcia et al, 2007; Nie et al, 2011). Phase contrast images of control cells of the three strains all present a homogenous surface.…”
Section: Resultsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 than 100 nm as shown in Figure 10; and we need to establish another method for measure the cross-linking depth. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 22 shows a higher contrast at the edge of the cross section, revealing that there is a layer more rigid 47 than the bulk of the PDMS. This layer ought to be the cross-linked PDMS resulted from the HHIC treatment.…”
Section: Mechanical Properties and Thickness Of Cross-linked Pdms Layermentioning
confidence: 88%
“…Atomic force microscopy (AFM) not only images the surface morphology, but also probes mechanical properties via phase shift imaging 46,47 . The mechanical properties of the HHIC treated PDMS substrates are also examined using a nanoindenter 48 .…”
Section: Introductionmentioning
confidence: 99%